The Meira Paibis of Manipus: Locating Agency - Salam, Bidyalaxmi (Indonesia Law Review, 2023)
‘Meira Paibi’ is an all-women grassroots resistance movement in Manipur (India). It emerged in 1980s against state atrocities committed under the ambit of the Armed Forces Special Powers Act, 1958 (AFSPA). Their ‘contentious politics’, protest rallies and demonstrations, have gained significant mainstream attention. Often than not, Meira Paibi’s image is interpreted as symbol of women’s empowerment. Women’s visibility in the public domain is not a new phenomenon in Manipur. Manipur had witnessed a number of women’s uprisings both during and post-colonial period. To conclude women’s engagements in the public domain as a sign of empowerment or passive victims in the face of socio-political undercurrents in the society is simplistic and a narrow frame. They are by no means passive victims. Meira Paibis exercise open resistance to state oppression, but also employ ‘everyday resistance’ towards other discriminatory practices. In everyday resistance, agency is less visible, hidden and usually inconsistent. This paper attempts to present everyday aspect of Meira Paibis. Their experiences and change agency are, however, diverse reflecting the heterogeneity within the movement.